IMPLEMENTASI KEBIJAKAN PENGELOLAAN TERUMBU KARANG DI KECAMATAN TAMBELAN KABUPATEN BINTAN - Dewanti Malasari E.21108020 (FISIP Universitas Tanjungpura, 2013)
This study focuses on standardization issues and target policies and resources in view of less effective. The focus of the research is trying to discuss using qualitative methods with case studies in sub Tambelan. Based on the results of the study found that the implementation of the policy on coral reef communities in the District Tambelan concerns and lack of socialization, coral reefs damaged by the bombing, lack of funds and time. Therefore, the researchers recommended that standards and targets to be clarified not only by regulation but a record of actions and attitudes to be clarified with the apparatus so that the rules apply not float and can be known and understood by the public, the government should give more severe sanctions, need to be made priorities according to the importance of the benefits of coral reef management objectives, providing a more viable means of transportation. The focus on resources both human resources, financial and time should be increased so that the implementation of policy implementation coral reefs become more optimal policy goals and targets that can be achieved. Keywords: Coral Reef Conservation, Benefits Coral Reef, Coral Reef bombing, Resource Control, Time-Distance Constraints